Studies of Heparin Binding to Antithrombin III by Crossed Immunoelectrophoresis - Barrowcliffe, Trevor W (Thrombosis and Haemostasis, 1979)
The technique of crossed immunoelectrophoresis has been used to study the binding to purified antithrombin III (At III) of heparin and other mucopolysaccharides. The technique was unable to detect differences among samples of whole heparin from various manufacturers, but proved useful in studying the binding of heparin fractions; at the same molarities, low and high molecular weight heparin fractions displayed equal binding ability to At III. A semi-synthetic heparin analogue showed no evidence of binding to At III, but a sample of heparan sulphate did interact with At III at a concentration 3 times that of heparin. Samples of purified At III from four different manufacturers all displayed heterogeneity with respect to heparin binding. A proportion of the total At III did not bind to heparin and, in one sample, this non-binding material constituted about 40% of the total. An antiserum made against purified At III contained antibodies with different cross-reactivities against heparin bound and non-heparin bound At III.